HUBUNGAN PENGETAHUAN ORANG TUA TENTANG STIMULASI PERKEMBANGAN DENGAN PERILAKU ORANG TUA DALAM MEMBERIKAN STIMULASI PERKEMBANGAN ANAK PADA USIA PRA SEKOLAH - Auza Mahira; Agnita Utami; Susi Erianti (Ensiklopedia Research and Community Service Review, 2025)
Optimal developmental stimulation in pre-school children plays an important role in supporting children's overall growth and development. However, in Indonesia, there are still many pre-school children who experience developmental delays, where one of the influencing factors is the role of parents. This study aims to determine the relationship between parents' knowledge about developmental stimulation and parents' behavior in providing stimulation of children's development at pre-school age at TK Pembina 03. The method used is quantitative which consists of a descriptive correlation design with a cross sectional approach. The sample of this study amounted to 93 parents who were selected using consecutive sampling technique. The instrument in this study used a questionnaire of knowledge about growth and development stimulation and parental behavior in providing growth and development stimulation. The analysis used was univariate and bivariate analysis. Bivariate analysis using chi-square test. The results of univariate analysis showed that respondents had an average age of 35.57 years, were all female (100%), with a high school education level (51.6%) and a housewife profession (63.4%). The majority had a good level of knowledge (63.4%), while the behavior in providing stimulation was quite active (46.2%). The results of bivariate analysis using the chi-square test showed a p value = 0.000 (0.05) so it can be concluded that there is a relationship between parental knowledge about developmental stimulation and parental behavior in providing stimulation of child development at pre-school age. The results of this study are expected to be input for TK Pembina 03 to work together and play an active role with parents in stimulating child development.Keywords: Parents, Knowledge, Behavior, Developmental Stimulation, and Pre-school Age